1999
DOI: 10.1080/1478601x.1999.9959537
|View full text |Cite
|
Sign up to set email alerts
|

Kentuckians’ changes in attitudes toward death penalty∗

Abstract: Using data collected in June, 1997 from a probability sample (N=709) of Kentucky's residents, the present paper examines the factors influencing attitudes toward death penalty and factors associated with changes in support for death penalty when alternative punitive measures for the offenders are presented. Confirming the conclusion drawn from several previous studies, our findings indicate that attitudes toward capital punishment are complex and multidimensional. While the majority of the population investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…As previously noted, studies conducted in Japan showed that the language used in surveys meant to assess public attitudes toward death penalty did make a real difference in the opinion polls’ outcomes (Bacon et al., 2017). Moreover, several research studies (Bohm et al., 1993; Dieter, 1997; Fox et al., 1991; Paternoster, 1991; Sandys and McGarrell, 1995;Vito et al., 1999) indicate that when respondents could choose between capital punishment and life in prison without the possibility of parole, public support for death penalty decreased substantially. Similar findings were obtained in other retentionist countries, such as China (Hood, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As previously noted, studies conducted in Japan showed that the language used in surveys meant to assess public attitudes toward death penalty did make a real difference in the opinion polls’ outcomes (Bacon et al., 2017). Moreover, several research studies (Bohm et al., 1993; Dieter, 1997; Fox et al., 1991; Paternoster, 1991; Sandys and McGarrell, 1995;Vito et al., 1999) indicate that when respondents could choose between capital punishment and life in prison without the possibility of parole, public support for death penalty decreased substantially. Similar findings were obtained in other retentionist countries, such as China (Hood, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies found that support for death penalty increases with age (Alston, 1976; Fox et al., 1991; Maggard et al., 2012), while other researchers noted that death penalty support decreases with age (Hessing et al., 2003). On the other hand, several studies could not identify any age effect (Jiang et al., 2010a, 2010b; Keil and Vito, 1991; Kelley and Braithwaite, 1990; Tyler and Weber, 1982; Unnever, 2010; Unnever and Cullen, 2006, 2007; Vito et al., 1999).…”
Section: Explaining Variations In Death Penalty Supportmentioning
confidence: 99%
See 3 more Smart Citations